Metastatic Prostate Cancer Mimicking Polymyalgia Rheumatica - Randazzo, Charles T. (Hindawi Publishing Corporation, 2011)
A 59-year-old male presented to the emergency department with a four-month progressive history of proximal muscle pain and weakness with elevated erythrocyte sedimentation rate and C-reactive protein. He was initially diagnosed with polymyalgia rheumatica (PMR) and admitted to the hospital. During his hospitalization he was found to have metastatic prostate cancer, which was thought to be responsible for his PMR-like syndrome. By recognizing the resemblance between metastatic malignancy and rheumatologic diseases, the emergency physician can improve diagnostic accuracy.